MALDI-TOF MS para diferenciação de isolados de Corynebacterium pseudotuberculosis biovar Ovis e Equi, e caracterização de uma nova espécie de Dietzia - Roselane Gonçalves dos Santos (2023)
Corynebacterineae is a suborder of Gram-positive, acid-alcohol resistant, usually aerobic, bacillary bacteria of the order Actinomycetales, which includes several genera such as Corynebacterium and Dietzia. Corynebacterium pseudotuberculosis is a bacterium of great veterinary importance that leads to great damage to agribusiness, requiring better biological knowledge to achieve disease control. On the other hand, species of the genus Dietzia are widely distributed in the environment, presenting an opportunistic role, with some species presenting an undetermined taxonomy. Biochemical, serological, and molecular methods have been developed for the laboratory diagnosis of diseases caused by C. pseudotuberculosis, however, the identification of the pathogen and the differentiation of biovars can sometimes be imprecise, and lead to taxonomic classifications with other bacteria, or vice versa, erroneously. In this study, we performed a MALDI TOF analysis to optimize the identification and differentiation of C. pseudotuberculosis biovars. Our data show that the MALDI TOF analysis is useful to identify C. pseudotuberculosis at the species and biovars level, as well as to identify other strains belonging to other genera/species, as was found in this work. During this optimization, we received a strain identified as C. pseudotuberculosis, however, the result of the quadruplex PCR, commonly used to identify C. pseudotuberculosis, was negative, and when we used the MALDI TOF for this identification, it was possible to identify it as a strain belonging to the genus Dietzia. Based on these findings, in this work we set out for the genomic characterization, performing the sequencing of the isolate, analysis of the genomic similarity between our isolate and the species of Dietzia available in public databases, phenotypic analysis of the strain, using as standard species already described for the genus, as well as some biochemical analyses. The results of the genomic analyses and physiological and biochemical tests used for the characterization of a new species determined that this strain is different from the known species of the genus Dietzia. Comparative genomic analyzes provide information on genomic diversity, taxonomy, and adaptation to the genus Dietzia and are a valuable resource for functional genomic studies, providing more comprehensive results than conventional ones, helping in the correct identification and improving the understanding of its opportunistic pathology. In addition, data from this work suggest that the isolate be classified as a representative of a new species of the genus Dietzia, called Dietzia calabriae.